Nilai-Nilai Pancasila Di Tengah Perubahan Peta Geopolitik Global: Analisis Kepentingan Nasional Dalam Pembentukan Kebijakan Hukum - Soepandji, Kris Wijoyo; Pulungan, M. Sofyan (UI Scholars Hub, 2022)
Pancasila as the basis of the state is the main guideline for Indonesian political and social life. In the field of law, Pancasila has been determined as the main source national legislation process. However, the competing interests in formulation of legal policies sometimes put Pancasila values at difficult position to be implemented. Indonesian lawmakers should end the unfavorable situation by utilizing geopolitical knowledge. Moreover, currently there is important change in the global geopolitical map which provides opportunity for Indonesia to make legal policies which are in accordance with its national interests. This research was conducted based on the inter-disciplinary legal research methodology by using a socio-legal approach for the data collection process. This research analyzes the natural resource sector which is very important for Indonesia, but vulnerable to foreign intervention. The result of the study finds the values of Pancasila in the midst of changes in the global geopolitical map can actually be implemented if the legal policy is mainly based on Indonesia's national interests.